2021
DOI: 10.1186/s12879-021-06196-3
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in seroprevalence rates of transfusion-transmitted diseases among blood donors in Jordan

Abstract: Background Hepatitis B and C infections and transmission are a serious challenge to all healthcare systems. We studied seroprevalence rates of Transfusion Transmitted Diseases (TTD) among blood bank donors in Jordan from 2014 to 2019 as a follow-up study of our previously published work. In addition, we wanted to explore the efficacy of the mandatory vaccination of infants against hepatitis B virus (HBV) which was implemented by the Ministry of Health since 1995 for the eradication of HBV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…The overall prevalence of anti-HBc in this study was 4.6%. Similar rates have been reported in Iran 4.9% 22 and Jordan (2.0-4.1%) 23 . Higher rates of anti-HBc positivity have been reported in studies conducted in Syria (10.3%) 24 .…”
Section: Discussionsupporting
confidence: 88%
“…The overall prevalence of anti-HBc in this study was 4.6%. Similar rates have been reported in Iran 4.9% 22 and Jordan (2.0-4.1%) 23 . Higher rates of anti-HBc positivity have been reported in studies conducted in Syria (10.3%) 24 .…”
Section: Discussionsupporting
confidence: 88%
“… 19 However, the seropositivity rate of the present study was higher than our previous study (1.9%). 16 A low prevalence of HBsAg was reported in Iraq (0.24%), 20 Jordan (0.3%), 21 and Malaysia (0.03%). 22 The present study revealed a lower prevalence rate of HBsAg than those reported rates in Saudi Arabia (3.24%), 23 Yemen (4.1%), 14 Sudan (5.8%), 24 Nigeria (5.8%), 25 Ethiopia (3.0%), 26 Cameroon (11.2%), 27 the Central African Republic (16.7%) 28 and Mauritania (11.8%).…”
Section: Discussionmentioning
confidence: 98%
“…33 Lower rates, however, were reported in studies in Iran 34 (4.9%), Saudi Arabia (5.7%), 35 and Jordan (2.0–4.1%). 21 …”
Section: Discussionmentioning
confidence: 99%
“…In the WHO's Eastern Mediterranean Region, it is estimated that 60 million people are infected with HBV [2]. Several hepatitis prevalence studies were conducted in Middle Eastern countries including Jordan [3][4][5]. In Jordan estimated population of the Kingdom by Administrative Divisions at end-year of 2021 was reported to be eleven million fifty-seven thousand [6].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015 the Jordanian National Blood Bank recorded a 2% of the unceasing screening for HBV infection among blood donors [9]. However, recent studies reported unexplained increment in the prevalence rates of HBV and hepatitis C virus (HCV) infections among blood donors in 2019 and among pregnant females in Jordan (5%) [5,10]. To add on, a recent cluster of new cases of acute hepatitis of unknown origin among young children in multi-countries were reported by the WHO [11].…”
Section: Introductionmentioning
confidence: 99%